Towards equality at work - Bhagyalakshi, J. (2005)
The International Labour Organisation formulates international labour standards in the form of Conventions and Recommendations setting minimum standards of basic labour rights. These include freedom of association, right to organize, collective bargaining, abolition of forced labour, equality of opportunity and treatment, and other standards regarding work related issues. An effective plan of action should focus on strengthening knowledge, advocacy and services. The articule emphasises that Governments and social partners should review their strategies with regard to recognizing and addressing discrimination on different grounds. - Reproduced.
Keywords: Equal opportunity